Vrnitev Arnoldove mačke - Lakner, Mitja (Obzornik za matematiko in fiziko, 2015)
A hyperbolic matrix yields a mapping on the torus. However we can, as V. I. Arnold V. I. Arnold and A. Avez, Ergodic problems in Classical Mechanics, Benjamin, New York, 1968 did, consider the picture of the cat on ?$N × N$? raster. After a certain number of iterations the cat returns. We are interested in the dependence of the period of return on the density of the raster net. The property of return can be used for coding and covering up information.
Keywords: mapping on the torus; preslikava na torusu; hiperbolična matrika; hyperbolic matrix; hiperbolični avtomorfizmi; hyperbolic automorphism; raster; raster net